1985
DOI: 10.1002/bit.260270521
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐down and optimization studies of the gluconic acid fermentation by Gluconobacter oxydans

Abstract: To simulate production-scale conditions of gluconic acid fermentation by Gluconobacter oxydans, different experimental setups are presented in this study. From the determination of the time constants of a production-scale reactor, it can be concluded that mixing and oxygen transfer are the rate-limiting mechanisms. This results in oxygen concentration gradients which were simulated in a one-compartment reactor in which the oxygen concentration was fluctuated by a fluctuated gassing with air and nitrogen. It co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 4 publications
1
42
0
1
Order By: Relevance
“…Around the mid-1980s, Kossen and co-workers using the concept of 'regime analysis', where the rate of oxygen uptake is compared with that of oxygen transfer and the level of dO 2 , suggested that, at the large scale, differences in dO 2 would be found in batch fermentations (see Oosterhuis et al, (1985) for example). Sometime later in the early 1990s, Enfors and co-workers came to similar conclusions for fedbatch fermentations with respect to the nutrient feed (see for example, ).…”
Section: B Operational Constraints At the Large-scalementioning
confidence: 99%
See 1 more Smart Citation
“…Around the mid-1980s, Kossen and co-workers using the concept of 'regime analysis', where the rate of oxygen uptake is compared with that of oxygen transfer and the level of dO 2 , suggested that, at the large scale, differences in dO 2 would be found in batch fermentations (see Oosterhuis et al, (1985) for example). Sometime later in the early 1990s, Enfors and co-workers came to similar conclusions for fedbatch fermentations with respect to the nutrient feed (see for example, ).…”
Section: B Operational Constraints At the Large-scalementioning
confidence: 99%
“…For simulating the phenomenon of poor spatial and temporal homogeneity at the large-scale, a technique used is to divide the large-scale reactor into two compartments, firstly by Kossens and co-workers (Oosterhuis et al, 1985) and later by Enfors and co-workers . The conditions established in each compartment depend on the type of poor mixing situation on the large-scale that is to be simulated.…”
Section: Small-scale Experimental Simulation Models Of the Large-smentioning
confidence: 99%
“…Breakthroughs have been made in hydrodynamics and mixing, modeling of two-phase gas/liquid biological processes (Guillard, 1999), large-scale microenvironment measurements (Bylund et al, 1998(Bylund et al, , 1999George, 1997;Manfredini et al, 1983;Oosterhuis and Kossen, 1984), and scale-down methodology studies (Oosterhuis et al, 1983(Oosterhuis et al, , 1985. The latter area of study includes the use of scale-down reactors (SDRs) with various biological model systems (Bylund et al, 1999;Fowler and Dunlop, 1989;George et al, 1993George et al, , 1998Larsson and Enfors, 1988;Moes et al, 1985;Neubauer et al, 1995a,b;Sweere et al, 1988a-c).…”
Section: Introductionmentioning
confidence: 97%
“…The first investigation involves the scale-down of aerobic batch cultivation in a continuous stirred tank reactor (CSTR) of 25 m 3 with Gluconobacter suboxydans (Oosterhuis et al, 1983(Oosterhuis et al, , 1985. This system is based on batch technique characteristics; that is, all substrates are in excess except for the oxygen that is fed to the process over time.…”
Section: Introductionmentioning
confidence: 99%
“…More than twenty years ago, Oosterhuis et al (1985) simulated production-scale conditions with respect to oxygen gradients by employing a two-compartment system, of which one compartment could be gassed with pure oxygen. The investigations in this system allowed valuable conclusions about oxygen uptake, growth and product formation rates of the studied organisms under different oxygenic conditions.…”
mentioning
confidence: 99%